Mechanical And Transport Properties Of Ultra High Performance Green Concrete Containing Ultra Fine Palm Oil Fuel Ash (Upofa) And Polyethylene Teraphthalate (Pet) Fibre - Qasim, Aktham Hatem (2020)
Reusing recycled waste materials in concrete mixtures as environment-friendly construction materials has been a concern of researchers in recent years. This research investigated the effects of integrating Ultrafine Palm Oil Fuel Ash (UPOFA) and Silica Fume (SF) with shredded recycled waste bottles in the form of Polyethylene Terephthalate (PET) on the properties of Ultra-High Performance Concrete (UHPC) and Ultra-High Performance Green Concrete (UHPGC). Studies on the effect of PET fibre inclusion in UHPC and UHPGC are limited. Therefore, this research aims to explore the effect of adding 1% PET fibre on the fresh, mechanical and transport properties of UHPC and UHPGC containing up to 50% of UPOFA and 20% of SF as a replacement binder with cement. UPOFA, with a particle size of 2 μm after the grinding and burning process was utilised in UHPGC production. Recycled waste beverage plastic bottles in the form of PET were shredded and utilised as fibre- reinforced materials in the production of Ultra-High-Performance PET- Reinforced Concrete (UHPPRC) and Ultra-High-Performance PET- Reinforced Green Concrete (UHPPRGC). Results showed that the presence of PET fibre reduced flowability and viscosity of UHPPRC and UHPPRGC compared with UHPC control mix. Moreover, the PET fibre content substantially improved the mechanical properties of UHPC and UHPGC. Compared with UHPC control mix, the largest compressive, splitting tensile and flexural strengths of beam were realised in UHPPRGC by 148.7, 8.28 and 19.096 MPa at 28 days and 154.2, 13.61 and 21.731 MPa at 90 days, respectively. Similarly, the PET fibre inclusion in UHPPRGC recorded the largest flexural load value for slab specimens at 28 days compared with UHPC control mix. In the same trend, the transport properties evaluated by porosity, initial surface absorption, water absorption and rapid chloride, gas and water permeability tests showed superior improvement achieved with the fiberised UHPPRGC containing (UPOFA-SF) and PET fibres at short (28 days) and long (90 days) terms. Thus, integrating PET fibres with pozzolanic material UPOFA and SF could promote to produce UHPC and UHPGC with adequate mechanical and superior durability properties.